Pernikahan Dini dan Dampaknya Tinjauan Batas Umur Perkawinan Menurut Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan - Ismail, La Ode (Universitas Batanghari Jambi, 2022)
Even though the age limit has been set, there are still deviations by carrying out underage marriages. This is clearly contrary to the principles and conditions of marriage outlined by Law Number 16 of 2019 concerning Marriage. Against this deviation, Law Number 16 of 2019 concerning Marriage provides a way out in the form of a dispensation from the court.In this study, the method used is normative empirical. This empirical normative legal research method is basically a combination of normative legal approaches with the addition of various empirical elements. Research results Amended in Law Number 16 of 2019 on Amendments to Law Number 1 of 1974 in Article 7 Paragraph (1) reads: